EFFECT OF USING LEAD RUBBER BEARING ON A STEEL ARCH BRIDGE - Kusumastuti, Dyah; Lim, E -; Asneindra, M; Mulyadi, Sandy (Fakultas Teknik Universitas Tanjungpura, 2022)
A study was conducted to evaluate the application of Lead Rubber Bearing (LRB) on bridge structures. The length of steel arch bridge is 80 m, width of 10 m, and height of 19.6 m. The bridge is simply supported with two bearings on each support. Structural analysis reveals that the lateral force on the bearing is more than 400 tons (835 tons in longitudinal direction). The original designer